Cdk5 drives formation of heterogeneous pancreatic neuroendocrine tumors - Angela M. Carter; Nilesh Kumar; Brendon Herring; Chunfeng Tan; Rachael Guenter; Rahul Telange; Wayne Howse; Fabrice Viol; Tyler R. McCaw; Hayden H. Bickerton; Priyanka Gupta; Frank Gillardon; et al. (Oncogenesis, 2021)
Abstract Pancreatic neuroendocrine tumors (PanNETs) are a heterogeneous population of neoplasms that arise from hormone-secreting islet cells of the pancreas and have increased markedly in incidence over the past four decades. Non-functional PanNETs, which occur more frequently than hormone-secreting tumors, are often not diagnosed until later stages of tumor development and have poorer prognoses. Development of successful therapeutics for PanNETs has been slow, partially due to a lack of diverse animal models for pre-clinical testing. Here, we report development of an inducible, conditional mouse model of PanNETs by using a bi-transgenic system for regulated expression of the aberrant activator of Cdk5, p25, specifically in β-islet cells. This model produces a heterogeneous population of PanNETs that includes a subgroup of well-differentiated, non-functional tumors. Production of these tumors demonstrates the causative potential of aberrantly active Cdk5 for generation of PanNETs. Further, we show that human PanNETs express Cdk5 pathway components, are dependent on Cdk5 for growth, and share genetic and transcriptional overlap with the INS-p25OE model. The utility of this model is enhanced by the ability to form tumor-derived allografts. This new model of PanNETs will facilitate molecular delineation of Cdk5-dependent PanNETs and the development of new targeted therapeutics.